Impact of copper and Emerging Technologies against Novel Coronavirus (Journal of Fiber Bioengineering and Informatics, 2021)
Coronavirus belongs to the novel virulent strains of the respiratory viruses. It is an invisible enemy having significant threats to human health. The major trouble is that the spread of coronavirus is not limited to its transmission from human to human (by contact, fomites, and droplets) but also continue to transmit from contaminated surfaces to humans. These infectious viruses can survive in different non- biocidal materials for a long time. Copper holds a significant position in different biological and biochemical processes because its ions Cu+2 and Cu+ can carry out oxidation, dioxygen transportation, and electron transference. It is a redox-active metal. It can convert into Cu+2 or Cu+ state by accepting or donating electrons. Reactive Oxygen Species (ROS) are generated on alloy surfaces. The redox reaction of copper (Cu+2 $\leftrightarrow$ Cu+) along with the generation of ROS results in enhanced inactivation of the virus. In this review, the effectiveness of copper against coronaviruses has been explained. The enaturing of specific proteins of coronavirus by the interaction of copper and its ions has also been reported. Hence, the copper coated surfaces could be used in public areas. Furthermore, the review represents the different techniques used for the coating of copper on conductive and non-conductive surfaces.
Keywords: SARS-CoV-2; anti-covid agents; COVID-19 respiratory disease; e±cacy of vaccine